Condensing Enzymes from Pseudoalteromonadaceae for Prodiginine Synthesis. Issue 11 (23rd April 2019) - Brass, Hannah U. C.; Klein, Andreas S.; Nyholt, Silke; Classen, Thomas; Pietruszka, Jörg
Abstract: Prodiginines are natural products that are produced by various microorganisms. As the biological activity of prodiginines varies depending on their structure, prodiginine derivatives are of interest. In order to extend the prodiginine structural diversity, new condensing enzyme homologs of PigC were analysed. The condensing enzyme PigC from S. marcescens catalyses the last step in prodiginine biosynthesis and accepts not only its natural substrate, but also synthetically produced monopyrroles. Still, the substrate spectrum of PigC is partially limited. In order to enable the biocatalytic production of new prodiginine derivatives, PigC homologs supplementing the substrate spectra of PigC are of interest. Two condensing enzymes homologs from two tambjamine producing Pseudoalteromonadaceae strains were analysed towards their catalytic ability to produce the structurally related prodiginines. Besides the investigation of their substrate spectrum and enzyme kinetic data, a preparative scale biocatalysis approach for the production of prodiginine derivatives was established, comparing different condensing enzymes. Abstract :